Revisiting growth and decline of late Quaternary mega-lakes across the south-central Tibetan Plateau. (15th November 2020) - Jonell, Tara N.; Aitchison, Jonathan C.; Li, Guoqiang; Shulmeister, James; Zhou, Renjie; Zhang, Haixia
Abstract: Lake basins record critical interactions between the hydrosphere, cryosphere and atmosphere. Their sediments and shoreline landforms archive timing, duration, and intensity of past climatic variability and environmental impacts over a variety of timescales. Thousands of lake systems spread across the internally drained Tibetan Plateau today, of which many are only the salty remains of much more expansive paleolakes in the past. This study presents new shoreline ages integrated with quantitative digital topographic analysis and regional geomorphic evidence to reconstruct the sizes and extents of late Quaternary rift lake systems for the south-central Tibetan Plateau. This study presents optically stimulated luminescence (OSL) and the first K-feldspar post-infrared infrared (pIRIR) stimulated luminescence ages for Zabuye Caka and Dawa Tso and tests if these lakes were once part of a singular Pleistocene mega-lake established across four N–S rift systems. Our new results show that two large but separate paleolake systems developed in the latest Pleistocene-earliest Holocene and no lake larger than ∼6460 km 2 has existed since at least 41 ka in the Lunggar region. Early Holocene paleolakes expanded up to 7× modern (+220–335 km 3 ) with two to four-fold asymmetric lake expansion in the west compared to the east. Findings corroborate earlier investigations, implying that dramatic runoff increase and/or evapotranspiration reduction prompted rapid earliest Holocene lake expansion. Precipitation variability, in combination with permafrost degradation, temperature and wind strength, governed paleolake moisture balance. Open-system lake behavior and evolving drainage configurations across complex topography explain delayed onsets of lake regression and punctuated lake decline. This suggests abrupt Holocene climate shifts are not necessarily required for punctuated lake decline. Lastly, unique geomorphological and paleoclimatic similarities between Tibetan and East African rift lakes highlight the potential for some Tibetan paleolakes to function as natural climate amplifiers over both short and geologic timescales. Highlights: South-central Tibetan paleolakes no larger than ∼6460 km 2 . Early Holocene paleolake expansion 2–7x modern (+220–335 km 3 ), with four-fold asymmetric expansion in west. Open-system behavior and paleolake fragmentation led delayed and punctuated lake response to climate variability. Some Tibetan rift lakes invoke comparison to East African Rift amplifier lakes.